The postmodern university? : contested visions of higher education in society (Buckingham : Society for Research into Higher Education and Open University Press, 1997)
This book is divided into two parts: Postmodernism versus Modernism; and The University in Society.
Keywords: Education; Social aspects; Educational change; Education, Higher -- Social aspects -- Great Britain -- Congresses; Education, Higher -- Social aspects -- United States -- Congresses; Educational change -- Great Britain -- Congresses; Educational change -- United States -- Congresses; Postmodernism and education